2022
DOI: 10.1039/d1ta09941h
|View full text |Cite
|
Sign up to set email alerts
|

Engineering a surface defect-rich Ti3C2 quantum dots/mesoporous C3N4 hollow nanosphere Schottky junction for efficient N2 photofixation

Abstract: Photo-driven fixation of nitrogen (N2) to ammonia (NH3) is a kinetically complex multielectron reaction process. The key to photocatalytic N2 fixation lies in designing photocatalysts with high photoinduced carriers separation...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 50 publications
1
28
0
Order By: Relevance
“…In 2022, the Ti 3 C 2 MQDs with the surfaces detect-rich/3D mesoporous C 3 N 4 were prepared by electrostatically self-assembly strategy (Fig. 11a) [76]. TEM image confirmed that the MQDs were uniformly dispersed on the surface of hollow C 3 N 4 (Fig.…”
Section: D Mqds/3d Nanomaterialsmentioning
confidence: 96%
See 1 more Smart Citation
“…In 2022, the Ti 3 C 2 MQDs with the surfaces detect-rich/3D mesoporous C 3 N 4 were prepared by electrostatically self-assembly strategy (Fig. 11a) [76]. TEM image confirmed that the MQDs were uniformly dispersed on the surface of hollow C 3 N 4 (Fig.…”
Section: D Mqds/3d Nanomaterialsmentioning
confidence: 96%
“…The defect sites with lower binding energy facilitate to promote the adsorption of N 2 molecules. In 2022, Chang et al [76] engineered a photocatalyst with Schottky junction and defects. The Ti 3 C 2 MQDs with amount of oxygen vacancies (OV) and Ti 3+ sites were anchored on the surface of mesoporous C 3 N 4 hollow nanosphere (Fig.…”
Section: Constructing Defects Of Mqds For Reactant Adsorptionmentioning
confidence: 99%
“…O v is one of the most important vacancies in the photocatalytic nitrogen fixation process. 33,67–71 It becomes the electron donor center in the photocatalytic process by virtue of its localized electron property, which increases the amount of N 2 capture and activation. Furthermore, oxygen vacancies can also be used to regulate the atomic arrangement and electronic structure of the catalyst surface, accelerate the separation of photogenerated carriers, inhibit their recombination, and allow more subsequent electrons to enter.…”
Section: Recent Catalyst Advances In Photocatalytic Nitrogen Fixationmentioning
confidence: 99%
“…The preparation methods of oxygen vacancies include the following: (1) heat treatment of polyols, NaOH and N 2 . 34,67,68,73 (2) The introduction of heteroatomic doping simultaneously generates oxygen vacancies. 91,92 (3) Ultraviolet photolysis.…”
Section: Recent Catalyst Advances In Photocatalytic Nitrogen Fixationmentioning
confidence: 99%
“…Depending on synthesis methods, functional groups on the surface can be modified to further tune the PL of CQDs. By introducing electron donor and/or electron acceptor, PL of CQDs can be quenched ( Wang et al, 2009 ; Basit et al, 2022 ; Chang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%